Implementasi Bodycam sebagai Instrumen Akuntabilitas dalam Tugas Keimigrasian di Indonesia - Sianipar, Passion Timothy Gerald (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Body-worn cameras (bodycams) are a technological innovation that plays a crucial role in strengthening the transparency and accountability of immigration duties in Indonesia. This study uses a descriptive qualitative method with a literature review of journals, regulations, and official reports to examine the effectiveness, challenges, and policy strategies related to bodycam use. The results show that bodycams can be an effective accountability instrument because they objectively record interactions between officers and the public, thereby increasing public trust and strengthening oversight mechanisms. However, implementation faces obstacles such as data storage infrastructure, operational costs, and organizational cultural resistance, particularly at busy service points such as Soekarno-Hatta Airport. Therefore, comprehensive regulations, personal data protection, and continuous evaluation are needed for bodycams to become an instrument for immigration institutional reform.